Estimating the global cost of vision impairment and its major causes: protocol for a systematic review. Issue 9 (6th September 2020) - Marques, Ana Patricia; Ramke, Jacqueline; Cairns, John; Butt, Thomas; Zhang, Justine H; Faal, Hannah B; Taylor, Hugh; Jones, Iain; Congdon, Nathan; Bastawrous, Andrew; Braithwaite, Tasanee; Jovic, Marty; et al.
Abstract : Introduction: Vision impairment (VI) places a burden on individuals, health systems and society in general. In order to support the case for investing in eye health services, an updated cost of illness study that measures the global impact of VI is necessary. To perform such a study, a systematic review of the literature is needed. Here we outline the protocol for a systematic review to describe and summarise the costs associated with VI and its major causes. Methods and analysis: We will systematically search in Medline (Ovid) and the Centre for Reviews and Dissemination database which includes the National Health Service Economics Evaluation Database. No language or geographical restriction will be applied. Additional literature will be identified by reviewing the references in the included studies and by contacting field experts. Grey literature will be considered. The review will include any study published from 1 January 2000 to November 2019 that provides information about costs of illness, burden of disease and/or loss of well-being in participants with VI due to an unspecified cause or due to one of the seven leading causes globally. Two reviewers will independently screen studies and extract relevant data from included studies. Methodological quality of economic studies will be assessed based on the British Medical Journal checklist for economic submissions adapted to costs of illness studies. This protocol has been prepared following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis protocols and has been published prospectively in Open Science Framework. Ethics and dissemination: Formal ethical approval is not required, as primary data will not be collected in this review. The findings of this study will be disseminated through peer-reviewed publications, stakeholder meetings and inclusion in the ongoing Lancet Global Health Commission on Global Eye Health. Registration details: https://osf.io/9au3w (DOI 10.17605/OSF.IO/6F8VM).